Pengaruh Lama Penyimpanan Terhadap Kadar Gula dan Vitamin C pada Buah Jeruk Siam ( Citrus nobilis var. microcarpa ) - Helmiyesi, Helmiyesi; Hastuti, Rini Budi; Prihastanti, Erma (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2008)
The aim of the research is to find out the effect of long storage against glucose and vitamin C degree andalso to find out how many days of the storage whioch can still maintain the glucose and vitamin C degreeupon siam orange ( Citrus nobilis var. microcarpa ). It is expected that the research may give anyinformation especially for the seller of siam orange about the effect of long storage against glucose andvitamin C degree and how many days the storage should be performed. The experimet includes 4 treatmentsand 5 repetilions. The treatment is the length of the storage, namely 0 day ( control ), 5 days, 10 days and 15days. The observed parameters are glucose, vitamin C degree and fruit weight decrease. The research usescomplete Random design, when there is a real difference Duncan test will be used upon significant degree of5 %. The result of the research indicates that the glucose degree of siam orange upon the storage of 5 and 10days increases compared to the control. Upon the storage of 15 days the glucose degree decreases comparedto the storage of 5 and upon the storage of 5 days does not change compared to the control, but it startsdecreasing upon the storage of 10 and 15 days.